Features of studying the gender of the noun of the Russian language in foreign groups - Dzhumanazarova Zilola Obidzhanovna; Dedakhanova Mukhaye Mutallievna; Baykhanova Shoira Dadakhanovna (International Journal on Orange Technologies, 2020)
The gender categories is one of the most complicated and mostly applied grammar structures in Russian grammar. The gender categories is usually identified based on the word endings. Most students learning Russian as a second language find this topic difficult to fully understand and truly apply in their speech. For this reason, it is essential to differentiate between the genders. The following article looks into this issue